Building Geographic Information Systems Tools for Reforestation Sites in Montgomery County, Maryland - Loescher, Dianna (My University, 2017)
This work added to the existing geographic information system database that the Maryland-National Capital Park and Planning Commission (M-NCPPC) had in place for their reforestation sites, developed a field accessible ArcCollector layer for information collection, and determined how repeatable the survey format was between two surveyors. Reforestation sites are important for the ecosystem services that trees provide which include filtering groundwater, supplying habitat for wildlife, and reducing flooding and surface runoff. It is important that the survey is capable of obtaining repeatable results, regardless of who performs the survey. Statistical analysis indicated that data fields pertaining to information on non-native invasive plant coverage and flood damage are less repeatable than others. To meet with M-NCPPC goals and objectives, it is not necessary to obtain a quantified value of non-native invasive plant cover and flood damage; however, other natural resource management teams may want to re-evaluate the importance of these field values if reusing this form in future surveys.